Study of spectrum of head and neck lesions diagnosed on fine needle aspiration cytology (FNAC) - Dr. Farah Jalaly Meenai; Dr. Rubal Jain; Dr. Sandeep Ojha; Dr. Gopal Krishna Sawke; Dr. Sonam Gupta (Tropical Journal of Pathology and Microbiology, 2018)
Background: Fine needle aspiration cytology (FNAC) is a cost effective and minimally invasive diagnostic outdoor procedure for head and neck lesions with high efficacy. Aims and objectives: To evaluate the spectrum of head and neck lesions with FNAC, its efficacy and correlating thefindings with histopathological diagnosis wherever possible. Materials and Methods: Retrospective observational study of 597 patients evaluated with FNAC for head and neck lesions from 2014 January to December 2016. Data were retrievedfrom the stored reports in Department Of Pathology and the results were analyzed. Clinical and radiological details were obtained from patients’ file wherever deemed necessary from Medical Record Department of the institute. Results: Most common site aspirated were Lymph nodes (64%) followed by Thyroid (18.3%), skin (5.7%) andsoft tissue (4.02%). Most common diagnosis in lymph node FNAC was metastatic lymphadenopathy (37.4%) followed by reactive lymphadenitis (31.9%) and granulomatous lymphadenitis (20.4%). Benign lesions were most common among thyroid swellings (70.1%)followed by papillary carcinoma (12.9%). Majority of salivary gland lesions were benign neoplasm (52.4%). Most common skin and soft tissuelesions were epidermal inclusion cyst (52.9%) and lipoma (66.7%) respectively. Histopathological diagnosis was available in 47.2% of cases with 94.7% concordance. Conclusion: Head and neck lesions are common superficial lesions that can be easily diagnosed oncytology. It differentiates inflammatory/infectionfrom neoplastic lesions and avoids unnecessary surgeries and expedites the management. FNAC is cost effective and accurate diagnostic procedure and can be recommended as a first line investigation.